Household-oriented benefits largely outweigh commercial benefits derived from cattle in Mabalane District, Mozambique - Karanja Ng'ang'a, Stanley; Ritho, Cecilia; Herrero, Mario; Fraval, Simon (Commonwealth Scientific and Industrial Research Organisation, 2018)
In Sub-Saharan Africa, research aimed at improving household livelihoods through cattle often targets commercial benefits while neglecting household-oriented benefits. The latter are rarely articulated, and their comprehensive role in livelihoods is little understood by policymakers. The main aim of this study was to assess household-oriented benefits of cattle as a basis for formulating appropriate policies. Data were collected from 192 households selected through multistage random sampling in Mabalane District of Mozambique in 2009. The main objectives of cattle raising were identified and ranked in order of importance by using the analytical hierarchy procedure. The vast majority (98%) of households kept cattle primarily to derive various types of household-oriented benefits such as draft power, financing, insurance, saving, social status and bridewealth. Only 2% of households kept cattle mainly for commercial benefits. The households secured financing, insurance and saving primarily by capital accumulation through herd expansion, for example after a good crop harvest, using the profit to purchase a young calf, an ox or a heifer. Households reporting social prestige as an important objective for raising cattle were mainly those already with high social status. In Mabalane District, a large herd of cattle is considered evidence of one’s ability to manage communally owned resources. This suggests that the functions of draft power, financing, insurance and saving play important roles in the livelihoods of most of agro-pastoral households in Mozambique—arguably more important than meat and milk. The reliance on financing, insurance and saving benefits of cattle, as well as the low level of milk and meat marketing, could be explained by the low level of development within the district, exacerbated by the civil war that ended in the 1990s.